Evaluation of Primary Production in the Lower Amazon River Based on a Dissolved Oxygen Stable Isotopic Mass Balance - Gagne-Maynard, William C.; Ward, Nicholas D.; Keil, Richard G.; Sawakuchi, Henrique O.; Da Cunha, Alan C.; Neu, Vania; Brito, Daimio C.; Da Silva Less, Diani F.; Diniz, Joel E. M.; De Matos Valerio, Aline; Kampel, Milton; Krusche, Alex V.; et al. (Frontiers in Marine Science, 2017)
The Amazon River outgasses nearly an equivalent amount of CO2 as the rainforest sequesters on an annual basis due to microbial decomposition of terrigenous and aquatic organic matter. Most research performed in the Amazon has been focused on unraveling the mechanisms driving CO2 production since the recognition of a persistent state of CO2 supersaturation. However, although the river system is clearly net heterotrophic, the interplay between primary production and respiration is an essential aspect to understanding the overall metabolism of the ecosystem and potential transfer of energy up trophic levels. For example, an efficient ecosystem is capable of both decomposing high amounts of organic matter at lower trophic levels, driving CO2 emissions, and accumulating energy/biomass in higher trophic levels, stimulating fisheries production. Early studies found minimal evidence for primary production in the Amazon River mainstem and it has since been assumed that photosynthesis is strongly limited by low light penetration attributed to the high sediment load. Here, we test this assumption by measuring the stable isotopic composition of O2 (δ18O-O2) and O2 saturation levels in the lower Amazon River from Óbidos to the river mouth and its major tributaries, the Xingu and Tapajós rivers, during high and low water periods. An oxygen mass balance model was developed to estimate the input of photosynthetic oxygen in the discrete reach from Óbidos to Almeirim, midway to the river mouth. Based on the oxygen mass balance we estimate that primary production occurred at a rate of 0.39 ± 0.24 g O m3 d-1 at high water and 1.02 ± 0.55 g O m3 d-1 at low water. This translates to 41 ± 24% of the rate of O2 drawdown via respiration during high water and 67 ± 33% during low water. These primary production rates are 2-7 times higher than past estimates for the Amazon River mainstem. It is possible that at high water much of this productivity signal is the result of legacy advection from floodplains, whereas limited floodplain connectivity during low water implies that most of this signal is the result of in situ primary production in the Amazon River mainstem.